The Effect of Supervision and Work Discipline on Teacher Performance (Study of Teachers at SMPN 18 Bandung) - Kurniasih, Ratna; Komar, Deden; Avianti, Widiya (Greenation Research & Yayasan Global Resarch National, 2024)
The aim of this research is to determine and analyze: (1) Supervision (2) Work Discipline; (3) Teacher Performance; and (4) The influence of supervision and work discipline on teacher performance at SMPN 18 Bandung City, both simultaneously and partially.The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is employees in the teacher environment at SMPN 18 Bandung City with a sample of 44 people. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that supervision of teachers at SMPN 18 Bandung City was good, work discipline among SMPN 18 Bandung City teachers could generally be said to be good, the performance of SMPN 18 Bandung City teachers was currently considered good. Supervision and Work Discipline simultaneously influence Teacher Performance at SMPN 18 Bandung City. However, work discipline partially influences performance rather than supervision. Because work discipline predominantly influences performance, being the first priority in improving performance, teachers at SMPN 18 Bandung City are expected to consistently maintain existing conditions, so that they are able to work more professionally.